35 years in plant lectin research: a journey from basic science to applications in agriculture and medicine - Van Damme, Els J. M. (Glycoconjugate journal, 2022)
Plants contain an extended group of lectins differing from each other in their molecular structures, biochemical properties and carbohydrate-binding specificities. The heterogeneous group of plant lectins can be classified in several families based on the primary structure of the lectin domain. All proteins composed of one or more lectin domains, or having a domain architecture including one or more lectin domains in combination with other protein domains can be defined as lectins. Plant lectins reside in different cell compartments, and depending on their location will encounter a large variety carbohydrate structures, allowing them to be involved in multiple biological functions. Over the years lectins have been studied intensively for their carbohydrate-binding properties and biological activities, which also resulted in diverse applications. The present overview on plant lectins especially focuses on the structural and functional characteristics of plant lectins and their applications for crop improvement, glycobiology and biomedical research.